Room-temperature electrochemical water–gas shift reaction for high purity hydrogen production - Xiaoju Cui (Nature Portfolio, 2019)
Traditional water–gas shift reaction process is hindered by harsh reaction conditions and extra steps for hydrogen separation and purification. Here, the authors report a room temperature electrochemical water–gas shift process for direct production of high purity hydrogen with a faradaic efficiency of approximately 100%.